PENGARUH PROMOSI DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN DETERJEN DAIA DI KOTA BATAM - harahap, puli hanafiah; Msi, Asron saputra (LPPM Universitas Putera Batam, 2021)
The case is about aims to known the influence of promotion and brand image on the decision to purchase Daia detergent in Batam City. The analysis in this study used independent variables as promotion, and brand image and dependent variables were purchasing decisions. The research samples are some of the consumers who bought daia detergent in Batam City. Samples using is accidental sampling method, which is a sampling technique by chance that everyone who accidentally met with researchers can be used as a sample, if it is felt that the person who happened to be encountered has certain characteristics needed by the researcher. The test results proved that the promotion result a significan and positiv effection on the purchase decision at a significance of 0.000 < 0.05, and the brand image had a significant and positive effect on the purchase decision, where there is a significance of 0.004 < 0.05 and simultaneousl the promotion and brand image had a significan influenc on the purchase decision with a significance value of 0.000 ​